2001
DOI: 10.1099/00221287-147-4-811
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum type A haemagglutinin-positive progenitor toxin (HA+-PTX) binds to oligosaccharides containing Galβ1-4GlcNAc through one subcomponent of haemagglutinin (HA1)

Abstract: Haemagglutinin (HA) activity of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…HA proteins appear to play an important role in absorption of PTC by interacting with oligosaccharides on intestinal epithelial cells (Fujinaga et al 1997;Fujinaga et al 2004;Inoue et al 2001;Kojima et al 2005;Nakamura et al 2007) (also see chapter 3). One Nacetylneuraminic acid (Neu5Ac) binding site has been reported in HA-70b of BoNT/C, which is located in a cleft formed by domains II and III (Nakamura et al 2009).…”
Section: Has Mediate Toxin-host Interactionsmentioning
confidence: 99%
“…HA proteins appear to play an important role in absorption of PTC by interacting with oligosaccharides on intestinal epithelial cells (Fujinaga et al 1997;Fujinaga et al 2004;Inoue et al 2001;Kojima et al 2005;Nakamura et al 2007) (also see chapter 3). One Nacetylneuraminic acid (Neu5Ac) binding site has been reported in HA-70b of BoNT/C, which is located in a cleft formed by domains II and III (Nakamura et al 2009).…”
Section: Has Mediate Toxin-host Interactionsmentioning
confidence: 99%
“…Only the 16 S toxin bound obviously to the epithelial cells and time to death after injection with 16 S toxin was measurably shorter compared with 12 S toxin or neurotoxin [13]. Furthermore, in a way comparable to 16 S toxin, recombinant proteins of HA1 and HA3 could bind both epithelial cells and erythrocytes [14,15]. Some monoclonal antibodies against HA1 reduced the 16 S toxin binding to the epithelial cells and neutralised the oral toxicity of small amounts of 16 S toxin [16].…”
Section: Introductionmentioning
confidence: 99%
“…The toxin titer (minimum lethal dose [MLD]/ml) was obtained by injecting the diluted preparation into three mice intraperitoneally, each receiving 0.5 ml. The HA titer was obtained by reacting twofold-diluted preparations with an equal volume of 1% neuraminidase-treated human erythrocytes in a microtiter plate (7,8). Peak 3 possessed both toxicity (8 ϫ 10 7 MLD/ml) and HA activity.…”
mentioning
confidence: 99%
“…Recently, it was found that serotype A and B HA-positive toxins could bind to both erythrocytes and the epithelial cells of the small intestine mainly via HA1 and that these bindings were effectively inhibited by lactose (3,8) (data concerning serotype B have not been published yet), indicating that HApositive toxins can bind to lactose via HA1. Based on these data, we planned to separate HA-positive 16S toxin and HAnegative 12S toxin by use of affinity gel column-linked lactose; it was speculated that the 12S toxin would pass through the showed both a high HA titer and toxicity, indicating that the former is 12S toxin and the latter is 16S toxin (Fig.…”
mentioning
confidence: 99%